(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the quality of life among the elderly with atrial fibrillation at Thong Nhat Hospital, Ho Chi Minh City in 2023. Methods: A cross-sectional descriptive study, evaluating the quality of life of 300 elderly inpatients (≥ 60 years old) with atrial fibrillation at Thong Nhat Hospital, Ho Chi Minh City from January 1, 2023 to December 31, 2023. Results: For overall health, 56.33% of patients had moderate to poor scores; low physical health scores (30.88 ± 24.13): mainly poor (54,33%) and moderate to poor (27,67%) scores; quite good mental health scores (60.91 ± 24.13): 69.33% of patients had moderate to good scores. Single/widowed subjects, with an education level of high school or less and a duration of atrial fibrillation of more than 1 year had significantly low quality of life in terms of physical health, mental health and general health (p<0.05). Conclusion: The overall assessment of quality of life among the elderly with atrial fibrillation was at an moderate - poor level. There were significant correlations between quality of life and marital status, education level and duration of atrial fibrillation.